The role of retreatment in the management of recurrent/progressive brain metastases: a systematic review and evidence-based clinical practice guideline - Ammirati, Mario (Springer US, 2009)
What evidence is available regarding the use of whole brain radiation therapy (WBRT), stereotactic radiosurgery (SRS), surgical resection or chemotherapy for the treatment of recurrent/progressive brain metastases? Target population This recommendation applies to adults with recurrent/progressive brain metastases who have previously been treated with WBRT, surgical resection and/or radiosurgery. Recurrent/progressive brain metastases are defined as metastases that recur/progress anywhere in the brain (original and/or non-original sites) after initial therapy. Recommendation Level 3 Since there is insufficient evidence to make definitive treatment recommendations in patients with recurrent/progressive brain metastases, treatment should be individualized based on a patient’s functional status, extent of disease, volume/number of metastases, recurrence or progression at original versus non-original site, previous treatment and type of primary cancer, and enrollment in clinical trials is encouraged. In this context, the following can be recommended depending on a patient’s specific condition: no further treatment (supportive care), re-irradiation (either WBRT and/or SRS), surgical excision or, to a lesser extent, chemotherapy. Question If WBRT is used in the setting of recurrent/progressive brain metastases, what impact does tumor histopathology have on treatment outcomes? No studies were identified that met the eligibility criteria for this question.